The Analysis of Figurative Language in Coldplay’s Parachutes Album - Amelia Yuli Astuti; Widia Astuti (Fakultas Sastra Universitas Ekasakti, 2020)
Figurative language is language that uses various kinds of figures. Figurative language is a form of using language in the form of a comparison or parable. This research analyze figurative language in Coldplay's song lyrics. The data source is taken from all song lyrics of Parachutes album by Coldplay. The purposes of this research are: (1) to describe the types of figurative language found in Coldplay song lyrics, (2) to explain the meaning of figurative language contained in the selected song lyrics, and (3) to find out the types of figurative language is dominantly used in Coldplay song lyrics. This research uses qualitative descriptive method. The data analysis of this research is to follow the following steps: selecting songs that contain figurative language, identifying types of figurative language by reading carefully, classifying types of figurative language from the data, and making conclusions. The results of this research show that the total number of figurative languages used in the lyrics of the song parachutes Coldplay is 35 types of figurative language. Which consists of: 2 simile, 3 repetition, 9 metaphor, 8 hyperbole, and 13 rhetoric. The type of figurative language most dominantly is rhetoric.